Transitioning from Status to Needs Based Assistance for Georgia IDPs : A Poverty and Social Impact Analysis - World Bank (World Bank, Washington, DC, 2016)
This report presents to the Government of Georgia (GoG) an analysis of the implications of potential policy changes to internally displaced person (IDP) assistance. A pressing question for policy makers in Georgia is the sustainability of status-based IDP assistance and what efforts can be made to tailor this assistance to favor the poor and vulnerable. Elimination of the IDP benefit has been subject to debate among policymakers. The World Bank has worked with the government to support improvements to the socioeconomic situation of IDPs in Georgia since 2008. The IDP Community Development Project, implemented between 2009-2012 improved service delivery, infrastructure, and livelihoods in over 40 IDP communities. Evidence on the socio-economic needs of IDPs has been collected by both government and donors; yet no comprehensive research has been conducted to critically compare their situation to that of the overall population. The objective of this research is to generate more evidence on the significance of the IDP benefit, and consequences that may be expected if this benefit is removed, in order to inform future policy decisions of the GoG in this regard. The report examines: (i) the policy and institutional framework and considerations that may support or obstruct a shift in IDP assistance; (ii) quantitative evidence on the socio-economic situation of IDPs as compared to non-IDPs in Georgia; and (iii) qualitative evidence on the significance of the IDP benefit, attitudes towards the benefit program, and vulnerabilities that may arise from its potential elimination. The paper concludes with policy recommendations for mitigating negative poverty and social impacts, should the government pursue a decision to remove the IDP benefit program.